MENINGKATKAN PERENCANAAN KARIER MELALUI BIMBINGAN KELOMPOK TEKNIK PEER GUIDANCE - Tsania Nujcha Silmi Nabila; Sumarwiyah; Edris Zamroni (Program Studi Bimbingan dan Konseling, 2025)
The success of a person's career achievement is influenced by the ability to plan a career and make mature decisions. Someone who has the ability to plan a career is certainly able to understand themselves. Thus, the individual can decide the most appropriate choice according to their circumstances. The objectives to be achieved in this study are as follows: (1) Describe the application of peer guidance technique group guidance in improving career planning for students at Assa'idiyyah Vocational School; (2) Describe the improvement in career planning for students at Assa'idiyyah Vocational School after being given peer guidance technique group guidance. This research was conducted at SMK Assa’idiyyah Kudus. The research subjects were eight students, who came from grades XI and XII from various expertise programs. The sampling technique used purposive sampling technique. The type of research used is Guidance and Counseling Action Research. Data collection techniques use observation and interviews. Data analysis uses quantitative descriptive. The results of the study showed that the career planning obtained by the research subjects before the provision of action was 31% with the category (Very Poor), after the provision of action through peer guidance technique group guidance in cycle I experienced an increase, with a score of 35% in the category (Poor) at the first meeting, then increased to 37% in the category (Poor) at the second meeting, and the third meeting increased with a score of 50% in the category (Enough). The study was continued in cycle II, with the results of observations at the first meeting of 53% in the category (Enough), the second meeting of 71% in the category (Good), and the third meeting of 81% in the category (Very Good).